The Long-term Effect of Superficial Bladder Neck Incision on Ejaculation and Incontinence in Boys with Primary and Secondary Bladder Neck Obstruction - Hennus, Pauline M. L.; Hoenjet, Esther; Kieft, Jan H.; de Jong, Tom P. V. M.; de Kort, Laetitia M. O. (Frontiers in Pediatrics, 2017)
Objective. Superficial bladder neck incision (SBNI) is controversial at young age, with retrograde ejaculation after puberty as main concern. The aim of the study is to investigate the long-term effect of SBNI on ejaculation and incontinence in boys with primary and secondary bladder neck obstruction. Materials and methods. In boys with infravesical obstruction, SBNI was performed in case of a persistent bladder neck obstruction after earlier desobstruction or in case of primary severely obstructive bladder neck. SBNI was performed with a diathermy hook, always superficially (2-3mm) and unilaterally at 7 o’clock. Males that had SBNI during childhood after PUV incision or relief of other obstruction between 1986 and 2003 were included. Evaluation was done by International Continence Society male sex questionnaire, International Prostate Symptom Score, developmental International Consultation Modular Questionnaire on Urinary Incontinence – Urinary Incontinence, frequency volume chart (FVC) and uroflowmetry. Results. Of 79 traceable patients, 40 (50.6%) participated. Of these, 37 (92.5%) completed all questionnaires and 28 (70%) performed uroflowmetry. Median age at SBNI was 4.7 (IQR 0.6-8.5) years and was 19.6 (IQR 17.3-20.9) years at follow-up. All men had antegrade ejaculation, 4/37 (10.8%) reported possibly reduced ejaculatory volume. Eight (22%) had moderate lower urinary tract symptoms (LUTS) and 2 (5.4%) moderate incontinence. Median Qmax was 30.1 (IQR 24.4-42.6) mL/s. Conclusions. SBNI in boys with severe infravesical obstruction can be done safely with preservation of antegrade ejaculation and no additional lower urinary tract dysfunction.